Discoid Lupus Erythematosus At Electrodesicccation - Jayashree R; Shenoi Shrutakirthi D; Sandra A (Wolters Kluwer Medknow Publications, 2001)
A 42 year old housewife developed erythematous papules with adherent scales over electrodesiccation sites on the face. Biopsy was suggestive of DLE.